2019
DOI: 10.1249/mss.0000000000001912
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of Cardiac Repolarization Instability during Exercise Testing

Abstract: Introduction Physical exercise triggers efferent cardiac sympathetic activation. Here, we tracked the spatiotemporal properties of cardiac repolarization on a beat-to-beat basis throughout a standardized exercise test and hypothesized a detectable change at the point of the anaerobic threshold (AT). Methods The study included 20 healthy adults (age 35.3 ± 6.7 yr) undergoing a standardized incremental exercise test on a cycle ergometer. During exercise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 21 publications
4
24
1
Order By: Relevance
“…In summary, we observed a link between potassium shifts during HD and PRD levels which indicates that removal of large amounts of potassium enhances the effect of efferent sympathetic activity on the ventricular myocardium. These changes were shown to be independent of changes in heart rates, a fact that has already been demonstrated in previous studies [8,10]. The independence of heart rate is important since fluid removal during HD per se might alter heart rate.…”
Section: Discussionsupporting
confidence: 74%
“…In summary, we observed a link between potassium shifts during HD and PRD levels which indicates that removal of large amounts of potassium enhances the effect of efferent sympathetic activity on the ventricular myocardium. These changes were shown to be independent of changes in heart rates, a fact that has already been demonstrated in previous studies [8,10]. The independence of heart rate is important since fluid removal during HD per se might alter heart rate.…”
Section: Discussionsupporting
confidence: 74%
“…These results improve those of previous works in which, although the reported errors were likewise lower than 50 W, the translation from Watts to minutes resulted in larger errors due to the nature of the exercise test. 12 When evaluated in terms of V O 2 , the mean estimation error was of 1% and 3% for dT and LFdT, respectively, being these errors lower than the inter-evaluator agreement in the visual determination reported in, 25 which was comprised within 3%-16%.…”
Section: Discussionmentioning
confidence: 73%
“…In this way, we established a priori precision of the Bland-Altman plot (ie, limits of agreement) of ±50 W, which is approximately the value obtained in. 12 With respect, to the bias, it should be kept within the limits of inter-evaluator error in the visual estimation of the ventilatory threshold, which has been reported to lie within 3 to 16% of…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, there was no correlation between heart rate changes and dT° as well as PRD changes. Previous studies showed that an increase of heart rate by means of fixed atrial pacing had no relevant effect on dT° and PRD levels (Rizas et al, 2014;Hamm et al, 2019). Furthermore, linear regression analysis excluded heart rate as a confounding factor for increased sympathetic activity associated repolarization instability.…”
Section: Discussionmentioning
confidence: 99%